Influence of carbon black on the mechanical and electrical properties of asphalt mixtures - Ahmedzade, Perviz; Geckil, Tacettin (Natl Inst Science Communication-Niscair, 2007)
The effect of carbon black used as a filler on the mechanical and electrically conductive properties of two types of asphalt mixtures was investigated. The asphalt mixtures in which carbon black and limestone fillers having the same aggregate gradation were prepared and optimum bitumen content was determined by Marshall stability test. Mechanical characteristics of the carbon black and control mixtures were evaluated by Marshall stability, indirect tensile stiffness modulus, creep stiffness, and indirect tensile strength tests. Based on these tests values it is clear that the best results were obtained from mixtures with carbon black filler. Obtained volume resistivity values of the all mixtures indicate that mixtures with carbon black filler have higher electrical conductivity than that of the control mixtures. The results of investigation showed that carbon black improves both mechanical and electrically conductive properties of the asphalt mixtures.